Enhancing Self-Regulated Learning Through Blended Learning: Insights from Educational Theories and Practices - Warnaningtyas, Murtiatmi; Sulisworo, Dwi; Toifur, Moh (The Indonesian Institute of Science and Technology Research, 2024)
The COVID-19 pandemic has forced us to transform traditional learning methods into online or distance learning. This shift has affected not only students but also teachers and parents. Face-to-face learning was replaced by the use of platforms such as Google Classroom, WhatsApp groups, and others. Students, who previously interacted directly with teachers, had to adapt to learning through Google Classroom or WhatsApp groups. This transition required students to develop their own learning patterns and self-regulated learning (SRL). By combining simple online learning via WhatsApp groups or Google Classroom with more interactive learning methods, students' SRL can be enhanced. Observations from teachers and responses from students indicate that blended learning has a positive impact on SRL among vocational high school students.